(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article examines the role of traditions and innovations, and also determines the prospects of music education in the formation of a socially and professionally significant personality. The main attention is paid to the constructive nature of the unity of traditions and innovations in music education.